Sulfur-containing benzofurans and α-pyrones from the mangrove-derived fungus Talaromyces sp. WHUF0341 - Zhang, Ruohan; Zhang, Jinxin; Huo, Ruiyun; Xue, Yaxin; Hong, Kui; Liu, Ling (Frontiers in Marine Science, 2022)
Two new sulfur-containing benzofurans, talarobenzofurans A and B (1 and 2), one new benzofuran talarobenzofuran C (3) and two new α-pyrones talaropyrones A and B (5 and 6), along with five known compounds eurothiocin A (4), nodulisporipyrone A (7), peniazaphilin B (8), ramulosin (9) and 6-hydroxyramulosin (10) were isolated and identified from the culture extract of the mangrove-derived fungus Talaromyces sp. WHUF0341 guided by OSMAC (one strain-many compounds) strategy. Their structures were established by extensive spectroscopic data analysis, the modified Mosher’s method and electronic circular dichroism (ECD) calculations. Structurally, compounds 1 and 2 possess the unique thioester moiety derived from benzofuran and 2-hydroxy-3-mercaptopropionic acid, which was rarely-observed in natural products. The α-glucosidase inhibitory, antibacterial and cytotoxic activities of the isolated compounds were evaluated. Compounds 3 and 4 exhibited inhibitory effects against α-glucosidase activity with IC50 values of 48.9 ± 2.16 and 8.8 ± 1.08 µM, respectively. The biosynthetic pathways of compounds 1−4 were also proposed.